Industrial training report: Honda Malaysia Sdn. Bhd - A Karim, Khairunisa (Faculty of Business and Management, 2025)
My unforgettable and eye-opening six-month industrial training begins here at Honda Malaysia Sdn. Bhd. I was chosen among other applicants to do my internship at Honda Malaysia Sdn. Bhd It was a very overwhelming and excited experience for me. I was placed as an intern in the Industrial Union and Relations (IUR) section. I have four members in my team which include a senior executive, an executive, a clerk and also an intern. I learned a lot of things such as drafted letters, key in the latecomer data, join meetings and supporting HR few HR events that were conducted by the HR Department. As an intern, I believe that by supporting other sections events, I’ll be able to expand my knowledge and gained variety of experiences. Honda Malaysia Sdn. Bhd. gave that chance to me. For my report, I had to do a SWOT Analysis consists of four components which are Strengths, Weaknesses, Opportunities and Threats. After I came out with the SWOT analysis, I had to provide solutions for every one of the components. It was challenging but nothing can beat you once you set your mind to it.